Neutron spectra at a high energy heavy ion accelerator measured with a TLD-based Bonner spectrometer. (20th October 2021) - Sokolov, A.; Kozlova, E.; Boscolo, D.; Durante, M.; Horst, F.; Radon, T.; Schuy, C.; Weber, U.
Abstract: A Bonner sphere spectrometer with TLD cards as sensitive elements was constructed and used at the GSI accelerator complex to measure the neutron spectral fluence rates for radiation safety purposes. The neutron spectra were measured in the synchrotron tunnel during 550 MeV/u 40 Ar beam operation and in Cave A experimental area with a 1 GeV/u 56 Fe beam impinging on a thick aluminum target. Unfolded spectra were compared with those calculated using the Monte Carlo code FLUKA. The measured spectra show a good agreement with the simulations and the set proved itself to be a useful tool for different radiation safety purposes.